Análisis de la educación para la ciudadanía global en organizaciones de la sociedad civil en el ámbito rural de Zaragoza - Belén DIESTE; Teresa COMA-ROSELLÓ; Ana Cristina BLASCO-SERRANO (Revista Iberoamericana de Estudios de Desarrollo)
Sustainable development goals (SDG) requires addressing the social complexity from active participation, where the global is based on the local. Civil society organizations (CSO) have a relevant role in global citizenship education (GCE) through networking, especially in rural areas, where the need for sustainable development becomes more evident. In this descriptive-exploratory analysis, the role of CSOs in the rural area of the province of Zaragoza is analyzed through a questionnaire on their performance in the surroundings and through their virtual spaces of communication. The results show the need for more planning and networking. The GCE actions address, in an interrelated manner, different SDGs and allow a new approach to the areas of intervention in line with the approach of the 2030 Agenda.